Refractive Outcomes After Descemet Membrane Endothelial Keratoplasty plus Cataract/Intraocular Lens Triple Procedure: A Fellow Eye Comparison - Augustin, Victor A.; Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2021)
Purpose: Descemet membrane endothelial keratoplasty is often combined with phacoemulsification and intraocular lens implantation (DMEK + cataract/IOL triple procedure) in phakic patients. This procedure results in a refractive shift that is difficult to predict. The aim of this study was to evaluate the hypothesis that the refractive shift in the second eye follows the shift in the first eye. Methods: In this retrospective, single-center, consecutive case series, the refractive outcomes of 254 eyes of 127 patients who underwent DMEK + cataract/IOL triple procedure in both eyes for Fuchs endothelial corneal dystrophy have been analyzed. Main outcome measures were spherical equivalent outcome (shift calculations), best spectacle-corrected visual acuity, central corneal thickness, and posterior simulated keratometry. Results: The mean best spectacle-corrected visual acuity before surgery was 0.51 +/- 0.24 and increased to 0.19 +/- 0.15 (logMAR) after surgery (P < 0.001). After surgery, a mean hyperopic shift of 0.98 +/- 0.89 D was observed. The refractive shift was 1.03 +/- 0.93 D and 0.92 +/- 1.02 D, in the first and second eyes, respectively (P = 0.435). In a paired analysis, the mean difference of the refractive shift between the first and second eyes was 0.49 +/- 0.43 D. Conclusions: In our fellow eye comparison, the refractive shift after DMEK + cataract/IOL triple procedure in the second eye was comparable with the shift in the first eye. As a consequence, the refractive outcome of the first eye might serve as a reference for optimizing the refractive target in the second eye. Further studies investigating the influence of corneal parameters on refractive shift are needed for a more predictable lens power selection.
CRIS-Team WoS Importer:2021-11-26